Tephra sedimentation and grainsize associated with pulsatory activity: the 2021 Tajogaite eruption of Cumbre Vieja (La Palma, Canary Islands, Spain) - Bonadonna, Costanza; Pistolesi, Marco; Dominguez, Lucia; Freret-Lorgeril, Valentin; Rossi, Eduardo; Fries, Allan; Biass, Sebastien; Voloschina, Marija; Lemus, Jonathan; Romero, Jorge E.; Zanon, Vittorio; Pastore, Camille; et al. (Frontiers in Earth Science, 2023)
Long-lasting eruptions are of complex characterization and are typically associated with challenging risk assessment and crisis management due to the usual occurrence of multiple interacting hazards evolving at different temporal and spatial scales (e.g., lava, tephra, and gas). The 2021 Tajogaite eruption of Cumbre Vieja (La Palma) demonstrated how even hybrid events that are mostly effusive can be associated with widespread and impacting tephra deposits as a result of a complex interplay among gas flux, conduit geometry, and magma feeding rate. In this novel study, direct observations, syn-eruptive and post-eruptive sampling, and statistical analysis of pulsatory activity have been combined to provide new insights into eruption dynamics. They show how rapid gas segregation and high magma ascent rate modulated the gas flux at multiple vents, resulting in short-time fluctuations among the different explosive styles (ash-poor gas puffing, Strombolian, violent Strombolian, and lava fountaining) and unsteady tephra ground accumulation. Various size-selective sedimentation processes were also observed, including particle aggregation and ash fingers, which have impacted the overall tephra dispersal. In fact, even though both local and total grainsize distributions of selected layers, units, and of the whole tephra blanket are unimodal with a low fine-ash content, grainsize analysis of 154 samples suggests no correlation of particles <63 μm with distance from vents. Our analyses demonstrate the need to include a detailed characterization of all products of hybrid eruptions for a comprehensive interpretation of eruptive dynamics and to use multiple classification strategies that can capture eruptive styles at different temporal scales.